2009
DOI: 10.1007/s00723-009-0094-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects in 94 GHz Orientation-Selected PELDOR on a Rigid Pair of Radicals with Non-Collinear Axes

Abstract: For aromatic organic radicals, pulsed electron-electron double resonance (PELDOR) experiments at high magnetic fields provide information not only about the distance between the paramagnetic species but also about their relative orientation. However, the three-dimensional biradical structure is encoded in a complex pattern of orientation-selected PELDOR traces and the execution of the experiment is generally aggravated by constraints posed by the available hardware and the intrinsically low modulation depth ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 18 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…4A ). 25 , 62 To gain insight into the location of NH 2 Y 731 ˙/R 411 A-α2, three sets of PELDOR experiments were recorded using broadband excitation with a high-power Q-band set up at different excitation positions in the EPR line 63 66 (see Fig. 4B and S8 † ).…”
Section: Resultsmentioning
confidence: 99%
“…4A ). 25 , 62 To gain insight into the location of NH 2 Y 731 ˙/R 411 A-α2, three sets of PELDOR experiments were recorded using broadband excitation with a high-power Q-band set up at different excitation positions in the EPR line 63 66 (see Fig. 4B and S8 † ).…”
Section: Resultsmentioning
confidence: 99%
“…A detailed study of the orientational selectivity at X-band has been performed for nitroxyl biradicals, [62][63][64][65] for Cu(II) ions and nitroxyl labels in porphyrin 61,64 and in spin-labeled proteins of tetramer KcsA. 66 The orientational selectivity is most notable in high frequency PELDOR spectroscopy, [67][68][69][70][71][72][73] due to the high g-factor resolution.…”
Section: Peldor Datamentioning
confidence: 99%
“…A commercial W-band resonator (Bruker TeraFlex) was used that allows for a maximal separation of pump and detection frequencies of 56 MHz at 400 mW of available microwave power (Bruker Power Upgrade 2). 12 For the RNA duplex (Fig. 2b, left), the orientation selection at 94 GHz shows clear deformations of the Pake patterns, with the parallel component of the dipolar tensor (D J ) appearing at resonances close to g z in the EPR spectrum and maximal modulation depth observed between g x and g y .…”
mentioning
confidence: 97%
“…This is not only due to the variety of possible conformations that some labels can adopt within the bio-macromolecule, but moreover, to the difficulties related to the performance of a two frequency pump-probe pulsed EPR experiment in the millimeter-wave range, as discussed in several recent papers. 7, [9][10][11][12][13][14][15] This bottleneck has prevented an extended examination of orientation selection at high frequencies in contrast to the method at low EPR frequencies (9 GHz). [16][17][18][19] Particularly, recent analysis of orientation selection at low frequencies revealed that the problem of reconstructing bi-radical structures based on triples of Euler angles is non-trivial due to ambiguities in the solutions.…”
mentioning
confidence: 99%